Chlorohydrocarbon repair material, preparation method thereof and method for in-situ repair of chlorohydrocarbon in aquifer

By preparing a chlorinated hydrocarbon remediation material in which organic matter A encapsulates organic matter B and C, and combining it with a fast-acting agent, the problem of chlorinated hydrocarbon remediation material loss in highly permeable sites was solved, achieving long-lasting sustained release and efficient remediation effects.

CN119263452AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310817562.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

In highly permeable sites, existing technologies suffer from rapid groundwater flow in aquifers, leading to the loss of emulsified oil agents and chlorinated hydrocarbon remediation materials in permeable reactive walls, resulting in unsustainable remediation effects.

Method used

A chlorinated hydrocarbon remediation material consisting of organic compounds A encapsulating organic compounds B and C is prepared into solid particles or blocks by controlling the molecular weight and weight ratio of the organic compounds. Combined with a rapid-starting agent, it is used for in-situ remediation of chlorinated hydrocarbons in aquifers.

Benefits of technology

It extends the effective action period of chlorinated hydrocarbon remediation materials, prevents agent loss, achieves long-term sustained-release electron donor function, and improves remediation efficiency and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263452A_ABST
    Figure CN119263452A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological stimulation repair of chlorinated organic pollutants in an aquifer, and discloses a chlorinated hydrocarbon repair material, a preparation method thereof and a method for in-situ repair of chlorinated hydrocarbon in the aquifer. The chlorinated hydrocarbon repairing material contains an organic matter A, an organic matter B and an organic matter C, wherein the organic matter A wraps the organic matter B and the organic matter C; the molecular weight of the organic matter A is 1000-30000, the molecular weight of the organic matter B is 200-2000, and the molecular weight of the organic matter C is 100-400. The method for preparing the chlorinated hydrocarbon repair material comprises the following steps: S1, under the protection of an inert atmosphere, carrying out first mixing on an organic matter A and an organic solvent, and then carrying out second mixing on an obtained first mixed solution, an organic matter B and an organic matter C; and S2, drying the second mixed solution obtained in the step S1. The chlorohydrocarbon repair material can maintain long-period operation of solid-phase reductive dechlorination components, and the effective slow-release period of the chlorohydrocarbon repair material can be remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biostimulation restoration of chlorinated organic pollutants in aquifers, and in particular to a chlorinated hydrocarbon restoration material and a preparation method thereof, and a method for in-situ restoration of chlorinated hydrocarbons in aquifers. Background Art

[0002] Aquifer pollution is common in my country, especially in shallow aquifers, and the pollution level is increasing and the scope of pollution is expanding. Among them, halogenated hydrocarbons are one of the more common organic pollutants. According to reports, in 2011, sampling and analysis of aquifers in 96 cities in my country found that halogenated hydrocarbons were the most frequently detected organic pollutants in nearly 93% of the urban aquifer samples. Among the halogenated hydrocarbon organic pollutants in my country's aquifers, trichloroethylene (TCE), carbon tetrachloride (CT), and tetrachloroethylene (PCE) are the most common. Similarly, in Europe, the United States, Japan and other countries and regions, TCE and PCE are also the most common organic pollutants in aquifers.

[0003] Chlorinated organic solvents are often widely used in industrial manufacturing processes such as degreasing, electronic parts cleaning and dry cleaning. Due to improper human management and disposal, chlorinated organic solvents often leak out and become common dense non-aqueous phase liquids (DNAPL) pollutants in aquifers. Since the density of dense non-aqueous phase liquids is heavier than water and they are immiscible with water or only slightly soluble in water, they will form an independent liquid phase after entering the aquifer. Once chlorinated hydrocarbons leak, they may be exposed to the environment through various channels such as drinking water, causing serious harm to the health of nearby people.

[0004] Traditional remediation technologies include aquifer extraction-treatment, in-situ thermal desorption, surfactant leaching, zero-valent iron chemical reduction and other technologies, but these technologies all have various problems, the most common of which are tailing and rebound problems during the remediation process. In order to solve the above pollution problems, many studies have used chlorinated hydrocarbons as target pollutants to develop in-situ biostimulation remediation technology that can treat DNAPL-contaminated aquifers. This technology is environmentally friendly, safe and economical. Its application in in-situ degradation of environmental pollutants is mainly to provide biodegradable organic matrix components to promote the growth of indigenous dechlorinating microorganisms to assist microbial decomposition of pollutants. Therefore, compared with physical and chemical remediation methods, it can relatively reduce the cost of remediation, is easy to operate and is more easily accepted by the general public. At the same time, in-situ biostimulation remediation technology belongs to in-situ remediation technology, which has little disturbance to the site, and since there is no need for ex-situ disposal in the process, it avoids the generation of wastewater and solid waste, and there is no concern about secondary damage to the environment such as chemical precipitation and the generation of a large amount of harmful sludge.

[0005] Chinese patent application CN114477474A discloses an in-situ remediation agent, preparation method and application for chlorinated hydrocarbon contamination in aquifers, wherein the remediation agent comprises zero-valent iron powder, biochar, biocarbon source, emulsifier, stabilizer and water, wherein the biocarbon source comprises short-acting, medium-acting and long-acting carbon sources, and the weight percentage of each component is: 20-45% zero-valent iron powder, 8-15% biochar, 15-35% biocarbon source, 1-3% emulsifier, 0.1-0.5% stabilizer and 15-30% water. Reusable oil and emulsifier are added to water, and the reusable oil and emulsifier are fully emulsified by low-speed stirring; zero-valent iron powder, biochar and stabilizer are added in sequence, and stirred to mix evenly; industrial syrup and straw powder are added, and mixed at a stirring speed of 2000r / min for 10-20min to obtain a remediation agent slurry, and the remediation agent is injected into the halogenated hydrocarbon contaminated water layer of the aquifer under high pressure.

[0006] Chinese patent application CN108675435A discloses a nano-emulsified carbon source with low aquifer permeability loss in aquifer restoration and a preparation method thereof, specifically disclosing that "the nano-emulsified carbon source is composed of water, edible vegetable oil and food-grade emulsifier; the mass ratio of food-grade emulsifier to edible vegetable oil is 1:(1-2); the food-grade emulsifier is a mixture of Tween-80 and Span-80, and the mass ratio of Tween-80 to Span-80 is 1:(0.2-0.5); the internal phase content is 5-35%. The preparation method is: mix the components in proportion, stir for 5-15 minutes, then ultrasonicate for 15-25 minutes, heat to 55-70°C, keep warm for 5-10 minutes, and cool naturally.

[0007] Chinese patent application CN109534517A discloses an emulsified vegetable oil and its preparation method and application, specifically disclosing that the emulsified vegetable oil includes the following weight percentage components: 45%-75% edible vegetable oil, 2%-12% surfactant and 20%-45% water; and optionally also includes a common substrate and / or a pH regulator. The preparation method of the emulsified vegetable oil includes the steps of mixed dissolution of soluble substrates, oil-water mixing and stirring; the application method of the emulsified vegetable oil includes the steps of injection well construction, preparation of emulsified oil liquid, evaluation of indigenous microbial activity, injection of emulsified oil liquid, etc., thereby achieving the standard remediation of aquifers polluted by chlorinated organic matter.

[0008] The prior art often uses vegetable oil and surfactant as raw materials, and uses ultrasound, mechanical stirring and other methods to prepare liquid emulsified oil. The emulsified oil prepared by this method has a good treatment effect and is widely used abroad. However, the particle size of the internal phase of the emulsified oil is mostly less than 10μm, or nanometer-level. In a high-permeability site, such as a site with a permeability coefficient greater than 1m / d, the rapid flow of groundwater in the aquifer will cause part of the emulsified oil agent to flow away with the groundwater, making it difficult to play the role of continuously supplying electron donors. In addition, when used in a permeable reaction wall, especially when the permeable reaction wall needs to maintain a high permeability to facilitate the flow of groundwater, the conventional emulsified oil agent will be lost from the permeable reaction wall as the aquifer flows, resulting in the effective action period of the permeable reaction wall becoming shorter, thereby failing. Summary of the invention

[0009] The purpose of the present invention is to overcome the problem that in existing high permeability sites, the groundwater in the aquifer flows faster, causing part of the emulsified oil agent to flow away with the underground flow, and when used in a permeable reaction wall, the chlorinated hydrocarbon repair material will flow from the permeable reaction wall with the flow of the aquifer, resulting in the failure of the permeable reaction wall. At the same time, the effective action period of the chlorinated hydrocarbon repair material is improved, and a chlorinated hydrocarbon repair material and a preparation method thereof and a method for in-situ repair of chlorinated hydrocarbons in an aquifer are provided. At the same time, the solid material can be made into granular or block form to meet the needs of different forms, and can keep the solid-phase reduction dechlorination component running for a long period of time, and its effective slow release period can be significantly increased.

[0010] In order to achieve the above-mentioned purpose, the present invention provides a chlorinated hydrocarbon repair material on one hand, which contains organic matter A, organic matter B and organic matter C, wherein the organic matter A encapsulates the organic matter B and the organic matter C; wherein the molecular weight of the organic matter A is 1000-30000, the molecular weight of the organic matter B is 200-2000, and the molecular weight of the organic matter C is 100-400.

[0011] Preferably, the weight ratio of the organic matter A, the organic matter B and the organic matter C is 30:0.5-20:0.1-3, preferably 30:1-15:1-2.

[0012] Preferably, the molecular weight of the organic matter A is 5000-20000.

[0013] Preferably, the organic substance A is a polymer; more preferably, the organic substance A is selected from one or more of polylactide, polyvinyl alcohol and polyalginic acid.

[0014] Preferably, the molecular weight of the organic matter B is 200-1500.

[0015] Preferably, the organic matter B is selected from one or more of vegetable oil, higher fatty acid and higher fatty acid ester.

[0016] Preferably, the molecular weight of the vegetable oil is 500-1500, preferably 700-1100.

[0017] Preferably, the vegetable oil is selected from one or more of soybean oil, peanut oil, rapeseed oil and sesame oil.

[0018] Preferably, the higher fatty acid is a C16-C18 fatty acid.

[0019] Preferably, the molecular weight of the higher fatty acid is 200-400, preferably 250-350.

[0020] Preferably, the higher fatty acid is selected from one or more of palmitic acid, stearic acid, palmitic acid and oleic acid.

[0021] Preferably, the higher fatty acid ester is a C16-C18 fatty acid ester.

[0022] Preferably, the molecular weight of the higher fatty acid ester is 600-1200, preferably 750-1000.

[0023] Preferably, the higher fatty acid ester is glyceryl stearate and / or glyceryl palmitate.

[0024] Preferably, the molecular weight of the organic matter C is 100-350.

[0025] Preferably, the organic substance C is low molecular weight polylactide.

[0026] Preferably, the chlorinated hydrocarbon repair material is a solid material.

[0027] Preferably, the chlorinated hydrocarbon repair material is in powder, granular or block form.

[0028] A second aspect of the present invention provides a method for preparing the chlorinated hydrocarbon repair material described above, the method comprising the following steps:

[0029] S1. Under the protection of an inert atmosphere, organic matter A is first mixed with an organic solvent, and then the obtained first mixed solution is second mixed with organic matter B and organic matter C;

[0030] S2. Drying the second mixed solution obtained in step S1.

[0031] Preferably, in step S1, the weight ratio of the organic matter A, the organic matter B and the organic matter C is 30:0.5-20:0.1-3.

[0032] Preferably, in step S1, the usage ratio of the organic substance A to the organic solvent is 5-50 g:100 mL, preferably 10-30 g:100 mL.

[0033] Preferably, in step S1, the organic solvent is one or more of ethanol, ethyl acetate and dichloromethane.

[0034] In step S1, the first mixing conditions include: a temperature of 35 to 85°C, preferably 50 to 65°C.

[0035] Preferably, in step S1, the second mixing conditions include: a temperature of 35 to 85°C, preferably 65 to 70°C.

[0036] In step S2, the drying conditions include: a temperature of 40-100°C, preferably 50-70°C.

[0037] Preferably, step S2 further comprises: drying step S2 to obtain a solid block product, and then optionally crushing the solid block product to obtain a powdered material.

[0038] Preferably, the particle size of the powdery material is 10 to 1000 μm.

[0039] Preferably, step S2 further comprises: drying step S2 to obtain a gel-like product, then molding the gel-like product to obtain spherical particles, freeze-drying the spherical particles to obtain a granular material, and then optionally crushing the granular material to obtain a powdery material;

[0040] Preferably, the freeze-drying conditions include: a temperature of -30 to -40°C and a time of 2 to 8 hours.

[0041] Preferably, the particle size of the powdery material is 10 to 1000 μm.

[0042] The third aspect of the present invention provides a chlorinated hydrocarbon repair material prepared by the method described above.

[0043] Preferably, the chlorinated hydrocarbon repair material is suitable for high permeability sites with a permeability coefficient greater than 1 m / d and special sites with high permeability in fractured aquifers.

[0044] A fourth aspect of the present invention provides a method for in-situ remediation of chlorinated hydrocarbons in an aquifer, the method comprising: mixing a chlorinated hydrocarbon remediation material, water and a quick-start agent, and then injecting the resulting mixed solution into a chlorinated hydrocarbon-contaminated water layer in the aquifer;

[0045] The chlorinated hydrocarbon repair material is the chlorinated hydrocarbon repair material described above;

[0046] The quick-start agent is selected from one or more of lactic acid, alginate, ethanol, ascorbic acid, citric acid and glucose.

[0047] Preferably, the weight ratio of the chlorinated hydrocarbon repair material to water is 1:2-20, preferably 1:2-15.

[0048] Preferably, the weight ratio of the chlorinated hydrocarbon repair material to the quick-start agent is 10 to 50:1, preferably 10 to 30:1.

[0049] Preferably, the method further comprises: adding a pH regulator during the mixing of the chlorinated hydrocarbon repair material, water and the quick-start agent.

[0050] Preferably, the pH adjuster is selected from one or more of Ca(OH)2, Mg(OH)2, CaCO3, MgCO3, Na2CO3 and NaHCO3, preferably CaCO3 and / or MgCO3.

[0051] Preferably, the chlorinated hydrocarbon is selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane, trichloropropane, dichloropropane, trichlorobenzene, dichlorobenzene and ethyl chloride.

[0052] A fifth aspect of the present invention provides a method for in-situ remediation of chlorinated hydrocarbons in an aquifer, the method comprising: mixing a chlorinated hydrocarbon remediation material and a quick-start agent, and then placing the mixture in a permeable reaction wall of a chlorinated hydrocarbon-contaminated water layer of the aquifer;

[0053] The chlorinated hydrocarbon repair material is the chlorinated hydrocarbon repair material described above;

[0054] The quick-start agent is selected from one or more of lactic acid, alginate, ethanol, ascorbic acid, citric acid and glucose.

[0055] Preferably, the weight ratio of the chlorinated hydrocarbon repair material to the quick-start agent is 10 to 50:1, preferably 10 to 30:1.

[0056] Preferably, the chlorinated hydrocarbon is selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane, trichloropropane, dichloropropane, trichlorobenzene, dichlorobenzene and ethyl chloride.

[0057] The present invention provides a controlled-release, long-life reduction and dechlorination composite repair material, which includes a medium-speed release agent and a slow-release agent, and the medium-speed release agent and the slow-release agent are wrapped by macromolecular degradable organic matter. The solid phase agent in the material can keep the solid-phase reduction and dechlorination component running for a long period of time, and its effective slow-release period can be significantly increased. At the same time, when the agent is used, an agent with a quick-start reduction and dechlorination function can be added, so as to quickly start the agent to carry out the process of reduction and dechlorination of chlorinated hydrocarbons; at the same time, the material can be solid particles or powder particles, which can be mixed with other materials of a permeable reaction wall in a high-permeability site or directly filled into a permeable reaction wall to ensure that the agent is not lost with groundwater, so as to achieve the purpose of long-term reduction and dechlorination, and can meet the needs of reduction and dechlorination at different stages, and the preparation method is simple; preferably, all the agent components are biodegradable components, and there is no secondary pollution problem. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 is a morphology image of the solid spherical particles prepared in step (2) of Example 1;

[0059] Figure 2 It is a schematic diagram of the structure of the test device used in Test Example and Example 8.

[0060] Reference numerals

[0061] 1 mixer 2 water storage container

[0062] 3 Peristaltic pump 4 Reaction soil column

[0063] 5 water outlet storage tank 41 sample injection port DETAILED DESCRIPTION

[0064] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0065] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0066] The present invention provides a chlorinated hydrocarbon repair material, which contains organic matter A, organic matter B and organic matter C, wherein the organic matter A encapsulates the organic matter B and the organic matter C; wherein the molecular weight of the organic matter A is 1000-30000, the molecular weight of the organic matter B is 200-2000, and the molecular weight of the organic matter C is 100-400.

[0067] The organic matter A in the chlorinated hydrocarbon repair material of the present invention physically wraps the organic matter B and the organic matter C, and the organic matter B and the organic matter C are mixed together. When the chlorinated hydrocarbon repair material repairs chlorinated hydrocarbons in an aquifer, the organic matter A, organic matter B and organic matter C will slowly (anaerobic) ferment in the underground aquifer, gradually degrade, and the organic matter B and organic matter C will be gradually released. The release rate of the organic matter B is relatively slow when used (called a slow-release agent), and the release rate of the organic matter C is relatively fast when used (called a medium-release agent). Through the coordination of specific organic matter B and organic matter C, controlled release is achieved, and the effect of long-term slow-release electron donor is achieved, thereby increasing the operating cycle of the reduction dechlorination component. In the present invention, "slow-release agent" and "medium-release agent" have no specific meanings, but are only used to illustrate the relative release rates of the two when used, that is, the release rate of the slow-release agent is lower than that of the medium-release agent.

[0068] In a preferred embodiment, the chlorinated hydrocarbon repair material described in the present application can be a solid material, which can prevent it from flowing with the flow of the aquifer during use, causing part of the material to flow away with the aquifer without playing the role of the corresponding electron donor; it can also prevent the material from being lost from the permeable reaction wall with the flow of the aquifer when used in the permeable reaction wall, causing the permeable reaction wall to fail.

[0069] Specifically, the morphology of the chlorinated hydrocarbon repair material is not limited, and can be powder, granular or block, etc., as long as it is solid and can be released normally when used. When used, different morphologies can be selected according to different usage scenarios. For example, if a permeable reaction wall is used, granular or block can be used; if a direct injection method is used, powder can be used.

[0070] In the chlorinated hydrocarbon repair material of the present invention, in order to make organic matter A, organic matter B and organic matter C play a role quickly when used, and at the same time make organic matter B and organic matter C play a slow release role and a medium-speed release role respectively, to achieve controlled release, and the chlorinated hydrocarbon repair material can be released continuously for a long time, to prevent the medium-speed release component from being released completely while the low-speed release component has not yet started to be released, it is necessary to limit the weight ratio of organic matter A, organic matter B and organic matter C to an appropriate range. In the present invention, the "slow" and "medium speed" have no specific meanings, but are only used to illustrate the relative rates of the two.

[0071] Specifically, the weight ratio of the organic matter A, the organic matter B and the organic matter C is 30:0.5-20:0.1-3, preferably 30:1-15:1-2, for example, 30:12:1.2, 30:1.5:0.3, 30:5:1.2, 30:9:1.2 and 30:10:1.2.

[0072] In the chlorinated hydrocarbon repair material of the present invention, specifically, the organic substance A can be a biodegradable organic substance with a molecular weight of 1000 to 30000, preferably a polymer with a molecular weight of 1000 to 30000. In a preferred embodiment, the molecular weight of the organic substance A is 5000 to 20000. In a more preferred embodiment, the organic substance A is a polymer; more preferably, the organic substance A is selected from one or more of polylactide, polyvinyl alcohol and polyalginic acid.

[0073] In a specific embodiment, the organic matter B may be a biodegradable organic matter with a molecular weight of 200 to 2000. In a preferred embodiment, the molecular weight of the organic matter B is 200 to 1500.

[0074] In a specific embodiment, the organic matter B is selected from one or more of vegetable oil, higher fatty acid and higher fatty acid ester.

[0075] In the present invention, the vegetable oil may be a common biodegradable vegetable oil in the art. Specifically, the molecular weight of the vegetable oil may be 500-1500, preferably 700-1100, for example, 700, 800, 900, 1000 or 1100.

[0076] Preferably, the vegetable oil is selected from one or more of soybean oil, peanut oil, rapeseed oil and sesame oil.

[0077] In the chlorinated hydrocarbon repair material of the present invention, the higher fatty acid may be a biodegradable higher fatty acid commonly found in the art. Specifically, the higher fatty acid may be a C16-C18 fatty acid. More specifically, the molecular weight of the higher fatty acid may be 200-400, preferably 250-350, such as 250, 256, 282, 284, 300, 312, 330 or 350. In a preferred embodiment, the higher fatty acid is selected from one or more of palmitic acid, stearic acid, palmitic acid and oleic acid.

[0078] In the chlorinated hydrocarbon repair material of the present invention, the higher fatty acid ester may be a biodegradable higher fatty acid ester commonly found in the art. Specifically, the higher fatty acid ester may be a C16-C18 fatty acid ester. Specifically, the molecular weight of the higher fatty acid ester may be 600-1200, preferably 750-1000, for example, 750, 760, 770, 880, 890, 900, 910, 920, 930, 940, 950 or 1000. Preferably, the higher fatty acid ester is stearic acid glyceryl ester and / or palmitic acid glyceryl ester.

[0079] In the chlorinated hydrocarbon repair material of the present invention, in order to better cooperate with the organic matter B, realize controlled release, achieve the effect of long-term sustained release of electron donors, and increase the operating cycle of the reduction and dechlorination component, the molecular weight of the organic matter C can be 50 to 400, preferably, the molecular weight of the organic matter C is 100 to 350. In a preferred embodiment, the organic matter C can be low molecular weight polylactide.

[0080] In order to obtain a long-acting slow-release electron donor in-situ repair material, the second aspect of the present invention provides a method for preparing the chlorinated hydrocarbon repair material described above, the method comprising the following steps:

[0081] S1. Under the protection of an inert atmosphere, organic matter A is first mixed with an organic solvent, and then the obtained first mixed solution is second mixed with organic matter B and organic matter C;

[0082] S2. Drying the second mixed solution obtained in step S1.

[0083] In the method of the present invention, organic matter A is dissolved in an organic solvent under the protection of an inert atmosphere, and then organic matter B and organic matter C are completely dissolved in the first mixed solution, and then the second mixed solution is dried. During the drying process, the degree of drying can be controlled according to the morphology of the material to be obtained. If a block material is required, the obtained mixture can be completely dried; if a granular material is required, the obtained mixture can be dried to a semi-solid state, thereby manually or mechanically forming balls. In this method, after organic matter A is dissolved in an organic solvent, organic matter B and organic matter C are completely dissolved or evenly dispersed in the above system. During the drying process, the organic solvent evaporates, and organic matter A returns to its original polymerization state, thereby encapsulating organic matter B and organic matter C.

[0084] In the method described in the present invention, in order to make the organic matter A, organic matter B and organic matter C in the obtained chlorinated hydrocarbon repair material play a role quickly when used, and at the same time make the organic matter B and organic matter C respectively play a slow sustained release role and a medium-speed sustained release role, to achieve controlled release, and the chlorinated hydrocarbon repair material can be released continuously for a long time to prevent the situation that the medium-speed release component has been released and the slow-speed release component has not yet started to be released, the weight of the organic matter A, organic matter B and organic matter C can be limited to an appropriate range.

[0085] Specifically, the weight ratio of the organic matter A, the organic matter B and the organic matter C is 30:0.5-20:0.1-3, preferably 30:1-15:1-2, for example, 30:12:1.2, 30:1.5:0.3, 30:5:1.2, 30:9:1.2 and 30:10:1.2.

[0086] In the present invention, in step S1, there is no particular restriction on the usage ratio of the organic matter A to the organic solvent, as long as the organic solvent is sufficient to dissolve the organic matter A, the organic matter B and the organic matter C, and in the subsequent steps, it is convenient to control the degree of drying of the obtained second mixed liquid according to the morphology of the material to be obtained.

[0087] In a preferred embodiment, the usage ratio of the organic substance A to the organic solvent may be 5-50 g:100 mL, preferably 10-30 g:100 mL.

[0088] In the present invention, the organic solvent may be an organic solvent well known in the art that can dissolve the organic matter A, the organic matter B and the organic matter C and is volatile.

[0089] Specifically, in step S1, the organic solvent is one or more of ethanol, ethyl acetate and dichloromethane. Preferably, in step S1, the organic solvent is ethanol, which is biodegradable and does not cause secondary pollution.

[0090] In a specific embodiment, the first mixing and the second mixing in step S1 are both performed under the protection of an inert atmosphere. Preferably, the inert atmosphere can be provided by nitrogen or an inert gas.

[0091] In a preferred embodiment, in step S1, the temperature of the first mixing can be 35-85° C., preferably 50-65° C. In step S1, the time of the first mixing is not particularly limited, as long as a milky white solution or a clear solution can be obtained after the organic matter A is mixed with the organic solvent.

[0092] In a specific embodiment, in step S1 , the order in which the first mixed liquid is mixed with the organic matter B and the organic matter C is not particularly limited, as long as the organic matter B and the organic matter C can be dissolved to obtain a uniform solution.

[0093] In a preferred embodiment, in step S2, the temperature of the second mixing can be 35 to 85°C, preferably 65 to 70°C. In step S2, there is no particular restriction on the time of the second mixing, as long as a uniform solution can be obtained after the first mixed solution is mixed with the organic matter B and the organic matter C. Preferably, in order to improve the mixing rate and mixing effect, in step S1, the first mixing and the second mixing are mixed under stirring conditions, that is, the first mixing and the second mixing are mixed by stirring. Specifically, the stirring mixing rate can be 100 to 1000 rpm.

[0094] In the present invention, in step S2, the drying method is not limited, and can be a conventional drying method in the art, as long as the organic solvent can be evaporated. In a specific embodiment, in step S2, the drying method is natural evaporation drying or heating drying.

[0095] Specifically, the temperature of the heating and drying is not limited, as long as the organic solvent can be evaporated and no loss is caused to macromolecular organic matter and low molecular organic matter.

[0096] In a specific embodiment, in step S2, the drying temperature may be 40-100°C, preferably 50-70°C.

[0097] In the present invention, for the drying process of step S2, the degree of drying, drying time and whether subsequent crushing is required can be selected according to the morphology of the material required for subsequent use.

[0098] In a specific embodiment, step S2 further includes: drying the second mixed solution obtained in step S1 to directly obtain a solid block product. No subsequent crushing is performed. When used, the block material and the quick-start agent can be directly mixed, and then the mixture can be placed in a permeable reaction wall of the chlorinated hydrocarbon contaminated water layer of the aquifer; or the block material and the quick-start agent are prepared into a mixed solution and injected into the chlorinated hydrocarbon contaminated water layer of the aquifer. The drying time of the solid block product obtained by heating and drying is not limited, as long as the mixed solution obtained in step S1 can be completely dried at the aforementioned heating and drying temperature to obtain a solid block product; preferably, the drying time is 30 minutes to 6 hours.

[0099] In a specific embodiment, step S2 further comprises: drying step S2 to obtain a solid block product, and then optionally crushing the solid block product to obtain a powdered material. When in use, the powdered material and the quick-start agent can be prepared into a mixed solution and injected into the chlorinated hydrocarbon-contaminated water layer of the aquifer. The drying time of the solid block product obtained by heating and drying is not limited, as long as the mixed solution obtained in step S1 can be completely dried at the aforementioned heating and drying temperature to obtain a solid block product; preferably, the drying time is 30 minutes to 6 hours. Specifically, the particle size of the powdered material can be 10 to 1000 μm.

[0100] In a specific embodiment, step S2 further comprises: drying step S2 to obtain a gel-like product, then molding the gel-like product to obtain spherical particles, freeze-drying the spherical particles to obtain a granular material, and then optionally crushing the granular material to obtain a powdery material. In order to obtain a gel-like semi-solid product, the drying time at the aforementioned heating and drying temperature is 20 minutes to 5 hours. The spherical particles can be centimeter-sized balls.

[0101] In the present invention, after obtaining the solid spherical particles, the solid spherical particles can be directly mixed with a quick-start agent without being crushed, and then the mixture is placed in a permeable reaction wall of a chlorinated hydrocarbon contaminated water layer in an aquifer; or the solid spherical particles and the quick-start agent are prepared into a mixed solution and injected into the chlorinated hydrocarbon contaminated water layer in an aquifer; or the powdery material obtained by crushing the solid spherical particles and the quick-start agent are prepared into a mixed solution and injected into the chlorinated hydrocarbon contaminated water layer in an aquifer. Specifically, the particle size of the powdery material can be 10 to 1000 μm.

[0102] Specifically, in order to obtain solid spherical particles, the freeze-drying conditions may include: a temperature of -30 to -40°C; and a time of 2 to 8 hours.

[0103] In the present invention, the pulverization of the solid block product or solid spherical particles can be carried out in a ball mill; the ball milling rate can be 1000-3000 r / min.

[0104] The third aspect of the present invention provides a chlorinated hydrocarbon repair material prepared by the method described above. The chlorinated hydrocarbon repair material is a controlled release, long-life reduction dechlorination composite repair material, which contains a medium-speed release agent and a slow-release agent. The agent is a solid phase component, which can keep the solid phase reduction dechlorination component running for a long period of time, and its effective slow-release period can be significantly increased. At the same time, when the agent is used, an agent for quickly starting the reduction dechlorination can be added, and the agent can be quickly started to carry out the chlorinated hydrocarbon reduction dechlorination process; at the same time, because the material can be solid, it can be directly mixed with other materials of the permeable reaction wall and filled into the permeable reaction wall to achieve the purpose of long-term reduction dechlorination, and can meet the needs of reduction dechlorination at different stages.

[0105] Under preferred conditions, the chlorinated hydrocarbon repair material prepared by the above method is suitable for high permeability sites with a permeability coefficient greater than 1m / d and special sites with high permeability in fractured aquifers. The permeability coefficient is determined by the steady flow pumping test method GB50027-2001 of the pumping well and the monitoring well.

[0106] The fourth aspect of the present invention provides a method for in-situ repair of chlorinated hydrocarbons in an aquifer, the method comprising: mixing a chlorinated hydrocarbon repair material, water and a quick-start agent, and then injecting the obtained mixed solution into the chlorinated hydrocarbon contaminated water layer of the aquifer; the chlorinated hydrocarbon repair material is the chlorinated hydrocarbon repair material described above; the quick-start agent is selected from one or more of lactic acid, alginate, ethanol, ascorbic acid, citric acid and glucose.

[0107] Specifically, the weight ratio of the chlorinated hydrocarbon repair material to water is 1:2-20, preferably 1:2-15, for example, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0108] Specifically, the weight ratio of the chlorinated hydrocarbon repair material to the quick-start agent may be 10 to 50:1, preferably 10 to 30:1, for example, 10:1, 15:1, 20:1, 25:1, or 30:1.

[0109] In the present invention, specifically, the preparation process of the mixed solution described in the fourth aspect includes: uniformly mixing the chlorinated hydrocarbon repair material and water, and then adding the quick-start agent and stirring and mixing to obtain a uniform mixed solution.

[0110] Specifically, the aforementioned chlorinated hydrocarbon repair materials, quick-start agents, and chlorinated hydrocarbon reduction dechlorination processes may produce various acidic substances. When preparing the mixed solution, a small amount of pH regulator may be added to adjust the pH value to avoid the mixed solution being injected into the aquifer to pollute the chlorinated hydrocarbon-contaminated water layer, and the chloride ions produced during the chlorinated hydrocarbon reduction dechlorination process causing the pH value in the water to decrease, thereby affecting the water layer environment.

[0111] Preferably, the method described in the fourth aspect further comprises: adding a pH regulator during the mixing process of the chlorinated hydrocarbon repair material, water and the quick-start agent.

[0112] Specifically, the pH adjuster can be various alkaline substances well known in the art. Preferably, the pH adjuster is selected from one or more of Ca(OH)2, Mg(OH)2, CaCO3, MgCO3, Na2CO3 and NaHCO3, more preferably CaCO3 and / or MgCO3.

[0113] In a specific embodiment, the chlorinated hydrocarbon is selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane, trichloropropane, dichloropropane, trichlorobenzene, dichlorobenzene and ethyl chloride.

[0114] The fifth aspect of the present invention provides a method for in-situ repair of chlorinated hydrocarbons in an aquifer, the method comprising: mixing a chlorinated hydrocarbon repair material and a quick-start agent, and then placing the mixture in a permeable reaction wall of a chlorinated hydrocarbon contaminated water layer in the aquifer; the chlorinated hydrocarbon repair material is the chlorinated hydrocarbon repair material described above; the quick-start agent is selected from one or more of lactic acid, alginate, ethanol, ascorbic acid, citric acid and glucose.

[0115] Specifically, the weight ratio of the chlorinated hydrocarbon repair material to the quick-start agent is 10 to 50:1, preferably 10 to 30:1, for example, 10:1, 15:1, 20:1, 25:1, or 30:1.

[0116] In a specific embodiment, the chlorinated hydrocarbon is selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane, trichloropropane, dichloropropane, trichlorobenzene, dichlorobenzene and ethyl chloride.

[0117] Specifically, various acidic substances may be generated during the aforementioned chlorinated hydrocarbon repair materials, quick-start agents, and chlorinated hydrocarbon reduction dechlorination process. When the chlorinated hydrocarbon repair materials and quick-start agents are mixed, a small amount of pH adjuster may be added for pH adjustment to avoid placing the mixture behind a permeable reaction wall of a chlorinated hydrocarbon-contaminated water layer in an aquifer to prevent the chloride ions generated during the chlorinated hydrocarbon reduction dechlorination process from causing the pH value in the water to decrease and affecting the water layer environment.

[0118] Preferably, the method described in the fifty-fourth aspect comprises: mixing a chlorinated hydrocarbon remediation material, a quick-start agent and a pH adjuster, and then placing the resulting mixture in a permeable reaction wall of a chlorinated hydrocarbon-contaminated water layer in an aquifer.

[0119] Specifically, the pH adjuster can be various alkaline substances well known in the art. Preferably, the pH adjuster is selected from one or more of Ca(OH)2, Mg(OH)2, CaCO3, MgCO3, Na2CO3 and NaHCO3, more preferably CaCO3 and / or MgCO3.

[0120] The chlorinated hydrocarbon repair material of the present invention is suitable for sites with fast aquifer flow rates, and is preferably used in sandy soil and silt soil.

[0121] The present invention will be described in detail below by way of examples, but the protection scope of the present invention is not limited thereto. Unless otherwise specified, the reagents used in the examples and comparative examples of the present invention are all commercially available products.

[0122] Examples 1-5 and Comparative Example 2 are used to illustrate the preparation process of chlorinated hydrocarbon repair materials.

[0123] Example 1

[0124] (1) Under the protection of nitrogen atmosphere and stirring of a heating magnetic stirrer, 10 g of polylactide with a molecular weight of 5000 and 100 mL of an ethanol solution with a concentration of 99% were added to a three-necked flask, and the mixture was stirred and heated at 65° C. for 20 minutes until the polylactide was completely dissolved to obtain a milky white or clear solution, and then 4 g of stearic acid with a molecular weight of 284 was added to the solution, and the mixture was stirred and heated at 65° C. for 10 minutes to obtain a uniform solution, and then 0.4 g of a low molecular weight polylactide with a degree of polymerization of 4 and a molecular weight of 306 was added to the solution, and the mixture was stirred and heated at 65° C. for 10 minutes to obtain a uniform solution, wherein the stirring speed of the heating magnetic stirrer is 1000 r / min;

[0125] (2) The mixed solution obtained in step S1 is heated at a constant temperature of 65° C. for 3 h until the ethanol is almost completely evaporated to obtain a gel-like semi-solid, which is then manually sphericalized to form centimeter-sized (about 1 cm in diameter) spherical particles. The spherical particles are then freeze-dried at a freeze-drying temperature of -40° C. for 2 h to obtain solid spherical particles (such as Figure 1 shown);

[0126] (3) The solid spherical particles are placed in a high-energy ball mill and ball-milled at a rotation speed of 2000 r / min for 15 min to obtain a powdered chlorinated hydrocarbon repair material A1 with a particle size distribution of 20-200 μm.

[0127] Example 2

[0128] (1) Under the protection of nitrogen atmosphere and stirring with a heating magnetic stirrer, 20 g of polylactide with a molecular weight of 10,000 and 100 mL of ethyl acetate solution with a concentration of 99% were added to a three-necked flask, and the mixture was stirred and heated at 50° C. for 20 minutes until the polylactide was completely dissolved to obtain a milky white or clear solution, and then 1 g of soybean oil was added to the solution, and the mixture was stirred and heated at 50° C. for 20 minutes to obtain a uniform solution, and then 0.2 g of low molecular weight polylactide with a degree of polymerization of 4 and a molecular weight of 306 was added to the solution, and the mixture was stirred and heated at 70° C. for 10 minutes to obtain a uniform solution, wherein the stirring speed of the heating magnetic stirrer is 500 r / min;

[0129] (2) The mixed solution obtained in step S1 is heated at a constant temperature of 50° C. for 30 minutes until the ethyl acetate is almost evaporated to obtain a gel-like semi-solid, which is then manually sphericalized to form centimeter-sized (about 1 cm in diameter) spherical particles, and then freeze-dried at a freeze-drying temperature of -30° C. for 4 hours to obtain solid spherical particles;

[0130] (3) The solid spherical particles are placed in a high-energy ball mill and ball-milled at a rotation speed of 2000 r / min for 3 min to obtain a powdered chlorinated hydrocarbon repair material A2 with a particle size distribution of 50-600 μm.

[0131] Example 3

[0132] (1) Under the protection of nitrogen atmosphere and stirring with a heating magnetic stirrer, 30 g of polylactide with a molecular weight of 2000 and 100 mL of ethanol solution with a concentration of 99% were added to a three-necked flask, and the mixture was stirred and heated at 65° C. for 20 minutes until the polylactide was completely dissolved to obtain a milky white or clear solution, and then 5 g of triglycerol stearate with a molecular weight of 891 was added to the solution, and the mixture was stirred and heated at 65° C. for 20 minutes to obtain a uniform solution, and then 1.2 g of low molecular weight polylactide with a degree of polymerization of 3 and a molecular weight of 234 was added to the solution, and the mixture was stirred and heated at 65° C. for 10 minutes to obtain a uniform solution, wherein the stirring speed of the heating magnetic stirrer is 500 r / min;

[0133] (2) The mixed solution obtained in step S1 is heated at a constant temperature of 70° C. for 2 h until the ethanol is almost evaporated to obtain a gel-like semi-solid, which is then manually sphericalized to form spherical particles with a diameter of 2 cm, and then the spherical particles are freeze-dried at a freeze-drying temperature of -40° C. for 4 h to obtain solid spherical particles;

[0134] (3) The solid spherical particles are placed in a high-energy ball mill and ball-milled at a rotation speed of 2000 r / min for 5 min to obtain a powdered chlorinated hydrocarbon repair material A3 with a particle size distribution of 30-400 μm.

[0135] Example 4

[0136] (1) Under the protection of nitrogen atmosphere and stirring with a heating magnetic stirrer, 5 g of polylactide with a molecular weight of 20,000 and 100 mL of 99% ethanol solution were added to a three-necked flask, and the mixture was stirred and heated at 70° C. for 20 minutes until the polylactide was completely dissolved to obtain a milky white or clear solution, and then 1.5 g of palmitic acid with a molecular weight of 256 was added to the solution, and the mixture was stirred and heated at 65° C. for 10 minutes to obtain a uniform solution, and then 0.2 g of low molecular weight polylactide with a degree of polymerization of 4 and a molecular weight of 306 was added to the solution, and the mixture was stirred and heated at 65° C. for 15 minutes to obtain a uniform solution, wherein the stirring speed of the heating magnetic stirrer is 500 r / min;

[0137] (2) The mixed solution obtained in step S1 is heated at a constant temperature of 65° C. for 2 h until the ethanol is almost completely evaporated to obtain a gel-like semi-solid, which is then manually sphericalized to form centimeter-sized (about 2 cm in diameter) spherical particles, which are then freeze-dried at a freeze-drying temperature of -40° C. for 4 h to obtain solid spherical particles;

[0138] (3) The solid spherical particles are placed in a high-energy ball mill and ball-milled at a rotation speed of 1000 r / min for 5 min to obtain a powdered chlorinated hydrocarbon repair material A4 with a particle size distribution of 40-500 μm.

[0139] Example 5

[0140] (1) Under the protection of nitrogen atmosphere and stirring with a heating magnetic stirrer, 15 g of polylactide with a molecular weight of 1000 and 100 mL of a dichloromethane solution with a concentration of 99% were added to a three-necked flask, and the mixture was stirred and heated at 70° C. for 10 minutes until the polylactide was completely dissolved to obtain a milky white or clear solution, and then 5 g of rapeseed oil was added to the solution, and the mixture was stirred and heated at 65° C. for 20 minutes to obtain a uniform solution, and then 0.6 g of a low molecular weight polylactide with a molecular weight of less than 200 was added to the solution, and the mixture was stirred and heated at 65° C. for 10 minutes to obtain a uniform solution, wherein the stirring speed of the heating magnetic stirrer is 500 r / min;

[0141] (2) The mixed solution obtained in step S1 is heated at a constant temperature of 65° C. for 10 minutes until the dichloromethane is almost completely evaporated to obtain a gel-like semi-solid, which is then manually sphericalized to form centimeter-sized (about 0.5 cm in diameter) spherical particles, which are then freeze-dried at a freeze-drying temperature of -40° C. for 4 hours to obtain solid spherical particles;

[0142] (3) The solid spherical particles are placed in a high-energy ball mill and ball-milled at a rotation speed of 2000 r / min for 5 min to obtain a powdered chlorinated hydrocarbon repair material A5 with a particle size distribution of 30-500 μm.

[0143] Comparative Example 1

[0144] The method of Example 1 is followed, except that in step (1), low molecular weight polylactide is not added. The specific method includes:

[0145] (1) Under nitrogen atmosphere protection and stirring with a heating magnetic stirrer, 10 g of polylactide with a molecular weight of 5000 and 100 mL of 99% ethanol solution were added to a three-necked flask, and the mixture was stirred and heated at 65° C. for 20 minutes until the polylactide was completely dissolved to obtain a milky white or clear solution, and then 4 g of stearic acid with a molecular weight of 284 was added to the solution, and the mixture was stirred and heated at 65° C. for 10 minutes to obtain a uniform solution, wherein the stirring speed of the heating magnetic stirrer was 1000 r / min;

[0146] (2) The mixed solution obtained in step S1 is heated at a constant temperature of 65° C. for 3 h until the ethanol is almost completely evaporated to obtain a gel-like semi-solid, which is then manually sphericalized to form centimeter-sized (about 1 cm in diameter) spherical particles, and then freeze-dried at a freeze-drying temperature of -40° C. for 2 h to obtain solid spherical particles;

[0147] (3) The solid spherical particles are placed in a high-energy ball mill and ball-milled at a rotation speed of 2000 r / min for 15 min to obtain a powdered chlorinated hydrocarbon repair material B1 with a particle size distribution of 20-200 μm.

[0148] Comparative Example 2

[0149] The method of Example 1 is followed, except that in step (1), stearic acid is not added. The specific method comprises:

[0150] (1) Under the protection of nitrogen atmosphere and stirring with a heating magnetic stirrer, 10 g of polylactide with a molecular weight of 5000 and 100 mL of ethanol solution with a concentration of 99% were added to a three-necked flask, and the mixture was stirred and heated at 65° C. for 20 minutes until the polylactide was completely dissolved to obtain a milky white or clear solution; then 0.4 g of low molecular weight polylactide with a degree of polymerization of 4 and a molecular weight of 306 was added to the solution, and the mixture was stirred and heated at 65° C. for 10 minutes to obtain a uniform solution, wherein the stirring speed of the heating magnetic stirrer was 1000 r / min;

[0151] (2) The mixed solution obtained in step S1 is heated at a constant temperature of 65° C. for 3 h until the ethanol is almost completely evaporated to obtain a gel-like semi-solid, which is then manually sphericalized to form centimeter-sized (about 1 cm in diameter) spherical particles, which are then freeze-dried at a freeze-drying temperature of -40° C. for 4 h to obtain solid spherical particles;

[0152] (3) The solid spherical particles are placed in a high-energy ball mill and ball-milled at a rotation speed of 2000 r / min for 15 min to obtain a powdered chlorinated hydrocarbon repair material B2 with a particle size distribution of 20-200 μm.

[0153] Test Case

[0154] The potassium dichromate method was used to determine the release of dissolved COD in the water phase to detect the effective action period of the powdered chlorinated hydrocarbon repair materials A1-A5 and B1-B2 prepared in Examples 1-5 and Comparative Examples 1-2. The test device used to detect dissolved COD in the water phase is as follows: Figure 2 As shown, the device includes: a water storage container 2, a stirrer 1, a peristaltic pump 3, a reaction soil column 4 (length 30 cm), and a water outlet water reservoir 5; wherein the stirrer 1, the water storage container 2, the peristaltic pump 3, the reaction soil column 4 and the water outlet water reservoir 5 are connected in sequence; the reaction soil column 4 is provided with a sample injection port 41, a water inlet and a water outlet, the water inlet is connected to the peristaltic pump 3, and the water outlet is connected to the water outlet water reservoir 5.

[0155] During the test, the powdered chlorinated hydrocarbon repair materials A1-A5 and B1-B2 samples to be tested are injected from the sample injection port 41, and then both sides of the samples to be tested are filled with quartz sand. The lower part of the water storage container 2 is filled with deionized water, and the upper part is filled with nitrogen to remove the oxygen in the headspace above the aqueous solution; the deionized water in the water storage container 2 is continuously injected into the reaction soil column 4 at a certain rate through the peristaltic pump 3, and the dissolved COD content data at the outlet of the reaction soil column 4 is regularly measured. The data are shown in Table 1-2.

[0156] It can be seen from Table 1 and Table 2 that the concentration of dissolved COD in the powdered chlorinated hydrocarbon repair materials prepared in Examples 1-5 is maintained at a relatively stable state from about 20 days to 300 days during the entire action cycle, indicating that the entire slow-release repair material maintains a continuous and stable release within the 300-day period, which is beneficial to provide a continuous carbon source for microorganisms and provide a good environment for the biological stimulation and degradation of chlorinated hydrocarbons.

[0157] However, the concentration of dissolved COD in the powdered chlorinated hydrocarbon repair materials prepared in Comparative Examples 1 and 2 was not stable during the entire action period of 300 days, indicating that the chlorinated hydrocarbon repair materials could not be released continuously and stably within the 300-day period.

[0158] Table 1 Dissolved COD test results

[0159] Dissolved COD / ppm initial 1 day 3 days 7 days 10 days 15 days 20 days Example 1 0.4 0.5 3 9 15 23 51 Example 2 0.5 0.2 3 7 21 17 26 Example 3 0.3 0.3 4 11 19 34 41 Example 4 0.6 0.6 2 5 15 26 30 Example 5 0.2 0.4 1 9 23 31 45 Comparative Example 1 0.5 0.6 1.1 2.6 3.8 4.6 18 Comparative Example 2 0.5 0.6 2 8 13 26 19

[0160] Table 2 Dissolved COD test results

[0161] Dissolved COD / ppm 30 days 50 days 80 days 140 days 200 days 300 days Example 1 52 53 51 51 59 48 Example 2 28 31 27 26 26 23 Example 3 45 41 48 58 36 39 Example 4 28 31 33 31 31 34 Example 5 51 45 52 53 52 46 Comparative Example 1 46 50 45 46 42 45 Comparative Example 2 15 5 4 2 1.5 0.9

[0162] Examples 6-10 and Comparative Examples 3-4 are used to simulate the process of in-situ remediation of chlorinated hydrocarbons in an aquifer using chlorinated hydrocarbon remediation materials.

[0163] Example 6

[0164] From the contaminated soil of a certain enterprise site, 1,1,2-trichloroethane contaminated aquifer sediments were obtained. The initial concentration of trichloroethane in the aquifer sediments was determined by GS-MS to be 50 mg / kg, and the water content of the sediments was 32%. The contaminated aquifer sediments were placed in a tube, sent to the laboratory, and directly placed in a glove box to avoid air contact during the whole process.

[0165] Accurately weigh 5 g of the powdered chlorinated hydrocarbon repair material A1 prepared in Example 1, place it in 10 g of deionized water, mix it evenly, then add 0.2 g of lactic acid and 0.3 g of glucose, continue to stir and mix evenly to obtain a mixed solution. Add the mixed solution into 2 kg of contaminated aquifer sediment, continue to stir evenly so that the whole system is in a slurry state.

[0166] Weigh 10 g of the above slurry state sample and place it in multiple headspace bottles, which are then placed in a constant temperature incubator for culture. The dissolved oxygen, redox potential and trichloroethane pollutant concentration are measured regularly. The data are shown in Table 3-8.

[0167] It can be seen from Tables 3 and 4 that the dissolved oxygen content dropped rapidly from the initial 0.6 ppm to below 0.3 ppm within 10 days, and from the 10th day to the 300th day, the dissolved oxygen content remained in a very low and relatively stable range.

[0168] It can be seen from Tables 5 and 6 that the redox potential decreased rapidly from the initial 120 mV to -50 mV on the 10th day, and then slowly decreased to -176 mV on the 50th day. The redox potential was relatively stable from the 50th day to the 300th day, indicating that due to the addition of electron donors in the process, the entire environment has been transformed from an oxidizing environment to a reducing environment. This environment provides better reducing conditions for the reductive dechlorination of chlorinated hydrocarbons, and the reductive dechlorination process is relatively stable.

[0169] As can be seen from Tables 7 and 8, the pollutant concentration did not change much from the initial 56ppm in the first 10 days, and basically remained around 50ppm. This may be due to the heterogeneity of the sediment and the reagent in the early mixing process and the systematic error in the test process. However, starting from the 30th day, the pollutant concentration changed significantly and decreased rapidly, indicating that after dozens of days of microbial growth, the dechlorination bacteria group has become the main colony structure, thereby quickly degrading chlorinated hydrocarbons, resulting in a rapid decrease in the concentration of chlorinated hydrocarbons.

[0170] Example 7

[0171] Contaminated soil was obtained from a certain enterprise site. The initial concentration of 1,1,2-trichloroethane in the aquifer sediment was determined by GS-MS to be 76 mg / kg, and the water content of the sediment was 28%. The contaminated aquifer sediment was placed in a tube, sent to the laboratory, and directly placed in a glove box to avoid air contact during the whole process.

[0172] Accurately weigh 5 g of the powdered chlorinated hydrocarbon repair material A2 prepared in Example 2, place it in 50 g of deionized water, mix it evenly, then add 0.3 g of ethanol and 2 g of Ca(OH)2 solid powder, continue to stir and mix evenly to obtain a mixed solution. Add the mixed solution to 2 kg of contaminated aquifer sediment, continue to stir evenly so that the whole system is in a slurry state.

[0173] Weigh 10 g of the above slurry state sample and place it in multiple headspace bottles, which are then placed in a constant temperature incubator for cultivation. The dissolved oxygen, redox potential and trichloropropane pollutant concentration are measured regularly. The data are shown in Table 3-8.

[0174] It can be seen from Tables 3 and 4 that the dissolved oxygen content dropped rapidly from the initial 0.7 ppm to below 0.2 ppm within 10 days, and from the 10th day to the 300th day, the dissolved oxygen content remained in a very low and relatively stable range.

[0175] It can be seen from Tables 5 and 6 that the redox potential decreased rapidly from the initial 204 mV to -40 mV on the 10th day, and then slowly decreased to -143 mV on the 50th day. The redox potential was relatively stable from the 80th day to the 300th day, indicating that due to the addition of electron donors in the process, the entire environment has been transformed from an oxidizing environment to a reducing environment. This environment provides better reducing conditions for the reductive dechlorination of chlorinated hydrocarbons, and the reductive dechlorination process is relatively stable.

[0176] As can be seen from Tables 7 and 8, the pollutant concentration did not change much from the initial 76ppm in the first 10 days, and basically remained around 70ppm. This may be due to the heterogeneity of the sediment and the reagent in the early mixing process and the systematic error in the test process. However, starting from the 30th day, the pollutant concentration changed significantly and decreased rapidly, indicating that after dozens of days of microbial growth, the dechlorination bacteria group has become the main colony structure, thereby quickly degrading chlorinated hydrocarbons, resulting in a rapid decrease in the concentration of chlorinated hydrocarbons.

[0177] Example 8

[0178] From the contaminated soil of a certain enterprise site, tetrachloroethylene contaminated aquifer sediments were obtained. The initial concentration of tetrachloroethylene in the aquifer sediments was determined by GS-MS to be 135 mg / kg, and the water content of the sediments was 30%. The contaminated aquifer sediments were placed in a tube, sent to the laboratory, and directly placed in a glove box to avoid air contact during the whole process.

[0179] Accurately weigh 5 g of the powdered chlorinated hydrocarbon repair material A3 prepared in Example 3, 0.2 g of ascorbic acid, and 5 g of NaHCO3 solid powder, mix them evenly, and place them in a Figure 2 Material filling position.

[0180] The soil column test was used to simulate the permeable reactive wall technology. The soil column was filled with tetrachloroethylene contaminated aquifer sediments. Figure 2 As shown, the inlet pollutant concentration is 100 ppm, and the effluent dissolved oxygen, redox potential and tetrachloroethylene pollutant concentration are measured. The results are detailed in Table 3-8.

[0181] It can be seen from Tables 3 and 4 that the dissolved oxygen content dropped rapidly from the initial 1.0 ppm to below 0.4 ppm within 15 days, and remained in a very low range in the subsequent 200 days.

[0182] It can be seen from Tables 5 and 6 that the redox potential decreased rapidly from the initial 106 mV to -80 mV within 30 days, and then slowly decreased to -172 mV on the 80th day. The redox potential was relatively stable from the 80th day to the 300th day, indicating that due to the addition of electron donors in this process, the entire environment has been transformed from an oxidizing environment to a reducing environment, which provides better reducing conditions for the reduction and dechlorination of chlorinated hydrocarbons.

[0183] As can be seen from Tables 7 and 8, the initial effluent concentration of the pollutant was 106 ppm, which did not change much in the first 15 days, and was basically maintained at around 100 ppm. This may be due to the heterogeneity of the sediment and the reagent in the early mixing process and the systematic error in the test process, but it can be explained that the pollutant concentration did not change significantly in this short period of time. However, starting from the 30th day, the pollutant concentration changed significantly and decreased rapidly, indicating that after dozens of days of microbial growth, the dechlorination bacteria group has become the main colony structure, thereby rapidly degrading chlorinated hydrocarbons, resulting in a rapid decrease in the concentration of chlorinated hydrocarbons.

[0184] Example 9

[0185] From the contaminated soil of a certain enterprise site, trichloropropane contaminated aquifer sediments were obtained. The initial concentration of trichloropropane in the aquifer sediments was determined by GS-MS to be 100 mg / kg, and the water content of the sediments was 32%. The contaminated aquifer sediments were placed in a tube, sent to the laboratory, and directly placed in a glove box to avoid air contact during the whole process.

[0186] Accurately weigh 5 g of the powdered chlorinated hydrocarbon repair material A4 prepared in Example 4, place it in 50 g of deionized water, mix it evenly, then add 0.5 g of lactic acid, continue to stir and mix evenly to obtain a mixed solution. Add the mixed solution into 2 kg of contaminated aquifer sediment, continue to stir evenly so that the whole system is in a slurry state.

[0187] 10 g of the above slurry state sample was weighed and placed in multiple headspace bottles, which were then placed in a constant temperature incubator for cultivation. The dissolved oxygen, redox potential and trichloropropane pollutant concentration were measured regularly. The results are shown in Table 3-8.

[0188] It can be seen from Tables 3 and 4 that the dissolved oxygen content dropped rapidly from the initial 0.9 ppm to below 0.3 ppm within 10 days, and in the subsequent 300 days, the dissolved oxygen content remained in a very low range.

[0189] It can be seen from Tables 5 and 6 that the redox potential decreased rapidly from the initial 89 mV to -86 mV within 20 days, and then slowly decreased to -140 mV on the 50th day. From the 140th day to the 300th day, the redox potential was relatively stable, indicating that due to the addition of electron donors in this process, the entire environment has been transformed from an oxidizing environment to a reducing environment, which provides better reducing conditions for the reduction and dechlorination of chlorinated hydrocarbons.

[0190] As can be seen from Tables 7 and 8, the pollutant concentration did not change much from the initial 100ppm in the first 15 days, and basically remained around 100ppm. This may be due to the heterogeneity of the sediment and the reagent in the early mixing process and the systematic error in the test process, but it can be explained that the pollutant concentration did not change significantly in this short period of time. However, starting from the 30th day, the concentration of the pollutant changed significantly and decreased rapidly, indicating that after dozens of days of microbial growth, the dechlorination bacteria group has become the main colony structure, thereby rapidly degrading chlorinated hydrocarbons, resulting in a rapid decrease in the concentration of chlorinated hydrocarbons.

[0191] Comparative Example 3

[0192] From the contaminated soil of a certain enterprise site, tetrachloroethylene contaminated aquifer sediments were obtained. The initial concentration of tetrachloroethylene in the aquifer sediments was determined by GS-MS to be 135 mg / kg, and the water content of the sediments was 30%. The contaminated aquifer sediments were placed in a tube, sent to the laboratory, and directly placed in a glove box to avoid air contact during the whole process.

[0193] Accurately weigh 5g of triglycerol stearate, 0.2g of ascorbic acid, and 5g of NaHCO3 solid powder, mix well, and place in Figure 2 Material filling position.

[0194] The soil column test was used to simulate the permeable reactive wall technology. The soil column was filled with tetrachloroethylene contaminated aquifer sediments. Figure 2 As shown, the inlet pollutant concentration is 100 ppm, and the effluent dissolved oxygen, redox potential and tetrachloroethylene pollutant concentration are measured. The results are detailed in Table 3-8.

[0195] It can be seen from Tables 3 and 4 that the dissolved oxygen content dropped rapidly from the initial 1.0 ppm to below 0.4 ppm within 3 days, and remained in a very low range in the subsequent 80 days. However, the concentration increased significantly from 140 days to 300 days in the later period. This may be due to the loss of triglycerol stearate as it dissolved in the aqueous phase and lost its degradation effect.

[0196] As can be seen from Tables 5 and 6, the redox potential rapidly decreased from the initial 109 mV to -79 mV within 20 days, and then slowly decreased to -162 mV on the 30th day, indicating that due to the addition of electron donors in the process, the entire environment has been transformed from an oxidizing environment to a reducing environment, which provides better reducing conditions for the reduction and dechlorination of chlorinated hydrocarbons. However, in the later period from 140 days to 300 days, the redox potential increased significantly, and the entire environment was transformed back into an oxidizing environment, which may be due to the loss of triglycerol stearate as it dissolved in the water phase and lost its degradation effect.

[0197] As can be seen from Tables 7 and 8, the pollutant concentration did not change much from the initial 106ppm in the first 7 days, and basically remained around 100ppm. This may be due to the heterogeneity of the sediment and the system errors in the test process during the early mixing process, but it can be explained that the pollutant concentration did not change significantly in this short period of time. From the 20th day, the pollutant concentration changed significantly, and the pollutant concentration decreased rapidly, indicating that after dozens of days of microbial growth, the dechlorination bacteria group has become the most important colony structure, thereby quickly degrading chlorinated hydrocarbons, resulting in a rapid decrease in the concentration of chlorinated hydrocarbons. However, in the later period, from the 80th day to the 300th day, the concentration gradually increased, which may be due to the loss of triglycerol stearate as it dissolved in the water phase, resulting in the loss of degradation.

[0198] Comparative Example 4

[0199] From the contaminated soil of a certain enterprise site, tetrachloroethylene contaminated aquifer sediments were obtained. The initial concentration of tetrachloroethylene in the aquifer sediments was determined by GS-MS to be 135 mg / kg, and the water content of the sediments was 30%. The contaminated aquifer sediments were placed in a tube, sent to the laboratory, and directly placed in a glove box to avoid air contact during the whole process.

[0200] Accurately weigh 5 g of the powdered chlorinated hydrocarbon repair material B2 prepared in Comparative Example 2, 0.2 g of ascorbic acid, and 5 g of NaHCO3 solid powder, mix them evenly, and place them in Figure 2 Material filling position.

[0201] A soil column test was used to simulate the permeable reactive wall technology. The soil column was filled with tetrachloroethylene-contaminated aquifer sediments. The soil column simulation test is shown in the figure. The influent pollutant concentration was 100 ppm. The effluent dissolved oxygen, redox potential and tetrachloroethylene pollutant concentration were measured regularly. The results are shown in Table 3-8.

[0202] It can be seen from Tables 3 and 4 that the dissolved oxygen content dropped rapidly from the initial 1.0 ppm to below 0.4 ppm within 10 days, and remained in a very low range in the subsequent 30 days. However, the concentration gradually increased from 50 days to 300 days in the later period. This may be because the powdered chlorinated hydrocarbon repair material B2 did not contain organic matter B, which degraded rapidly and lost its degradation effect.

[0203] As can be seen from Tables 5 and 6, the redox potential rapidly decreased from the initial 106mV to -104mV within 20 days, and then slowly decreased to -162mV on the 50th day, indicating that due to the addition of electron donors in the process, the entire environment has been transformed from an oxidizing environment to a reducing environment, which provides better reducing conditions for the reduction and dechlorination of chlorinated hydrocarbons. However, the concentration increased significantly from the 50th day to the 300th day, which may be due to the fact that the powdered chlorinated hydrocarbon repair material B2 did not add organic matter B, degraded rapidly, and lost its degradation effect.

[0204] As can be seen from Tables 7 and 8, the pollutant concentration did not change much from the initial 106ppm in the first 7 days, and basically remained around 100ppm. This may be due to the heterogeneity of the sediment and the systematic error in the test process during the early mixing process, which can be explained that the pollutant concentration did not change significantly in this short period of time. On the 20th day, the pollutant concentration changed and decreased, indicating that after dozens of days of microbial growth, the dechlorination bacteria group has become the most important colony structure, thereby quickly degrading chlorinated hydrocarbons, resulting in a rapid decrease in the concentration of chlorinated hydrocarbons. However, the concentration increased significantly after 50 days in the later period. This may be due to the fact that the powdered chlorinated hydrocarbon repair material B2 did not add organic matter B, degraded rapidly, and lost its degradation effect.

[0205] Table 3 Dissolved oxygen test results

[0206] Dissolved oxygen content ppm initial 1 day 3 days 7 days 10 days 15 days 20 days Example 6 0.6 0.7 0.7 0.4 0.3 0.3 0.3 Example 7 0.7 0.6 0.8 0.6 0.2 0.2 0.3 Example 8 1.0 0.8 0.9 0.6 0.5 0.4 0.4 Example 9 0.9 0.7 0.6 0.5 0.3 0.2 0.3 Comparative Example 3 1.0 / 0.4 0.3 0.3 0.2 0.3 Comparative Example 4 1.0 / 0.7 0.5 0.4 0.5 0.4

[0207] Table 4 Dissolved oxygen test results

[0208]

[0209]

[0210] Table 5 Oxidation-reduction potential test results

[0211] Redox potential mV initial 1 day 3 days 7 days 10 days 15 days 20 days Example 6 120 110 98 53 -50 -80 -110 Example 7 204 207 210 96 -40 -60 -90 Example 8 106 98 103 76 23 -26 -56 Example 9 89 67 75 55 -26 -46 -86 Comparative Example 3 109 / 76 25 -46 -49 -79 Comparative Example 4 106 / 99 68 15 -48 -104

[0212] Table 6 Oxidation-reduction potential test results

[0213] Redox potential mV 30 days 50 days 80 days 140 days 200 days 300 days Example 6 -130 -176 -186 -167 -184 -183 Example 7 -105 -143 -176 -184 -174 -168 Example 8 -80 -106 -172 -180 -179 186 Example 9 -102 -140 -156 -179 -178 -180 Comparative Example 3 -162 -176 -179 56 96 99 Comparative Example 4 -146 -162 -96 29 25 69

[0214] Table 7 Pollutant concentration data

[0215]

[0216]

[0217] Table 8 Pollutant concentration data

[0218] Pollutant concentration ppm 30 days 50 days 80 days 140 days 200 days 300 days Example 6 19 8 5 1 0.5 0.8 Example 7 35 32 18 5 4 2.8 Example 8 36 34 24 20 18 21 Example 9 46 38 29 10 4 2.5 Comparative Example 3 58 46 12 49 59 79 Comparative Example 4 52 37 42 74 91 86

[0219] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A chlorinated hydrocarbon repair material, characterized in that: The chlorinated hydrocarbon repair material contains organic matter A, organic matter B and organic matter C, wherein the organic matter A encapsulates the organic matter B and the organic matter C; wherein the molecular weight of the organic matter A is 1000-30000, the molecular weight of the organic matter B is 200-2000, and the molecular weight of the organic matter C is 100-400.

2. The chlorinated hydrocarbon repair material according to claim 1, characterized in that: The weight ratio of the organic matter A, the organic matter B and the organic matter C is 30:0.5-20:0.1-3, preferably 30:1-15:1-2.

3. The chlorinated hydrocarbon repair material according to claim 1 or 2, characterized in that: The molecular weight of the organic matter A is 5000 to 20000; Preferably, the organic substance A is a polymer; more preferably, the organic substance A is selected from one or more of polylactide, polyvinyl alcohol and polyalginic acid.

4. The chlorinated hydrocarbon repair material according to any one of claims 1 to 3, characterized in that: The molecular weight of the organic matter B is 200 to 1500; Preferably, the organic matter B is selected from one or more of vegetable oil, higher fatty acid and higher fatty acid ester.

5. The chlorinated hydrocarbon repair material according to any one of claims 1 to 4, characterized in that: The molecular weight of the vegetable oil is 500 to 1500, preferably 700 to 1100; Preferably, the vegetable oil is selected from one or more of soybean oil, peanut oil, rapeseed oil and sesame oil.

6. The chlorinated hydrocarbon repair material according to any one of claims 1 to 5, characterized in that: The higher fatty acid is a C16-C18 fatty acid; Preferably, the molecular weight of the higher fatty acid is 200 to 400, preferably 250 to 350; Preferably, the higher fatty acid is selected from one or more of palmitic acid, stearic acid, palmitic acid and oleic acid.

7. The chlorinated hydrocarbon repair material according to any one of claims 1 to 6, characterized in that: The higher fatty acid ester is a C16-C18 fatty acid ester; Preferably, the molecular weight of the higher fatty acid ester is 600 to 1200, preferably 750 to 1000; Preferably, the higher fatty acid ester is glyceryl stearate and / or glyceryl palmitate.

8. The chlorinated hydrocarbon repair material according to any one of claims 1 to 7, characterized in that: The molecular weight of the organic matter C is 100 to 350; Preferably, the organic substance C is low molecular weight polylactide.

9. The chlorinated hydrocarbon repair material according to any one of claims 1 to 8, characterized in that: The chlorinated hydrocarbon repair material is a solid material; preferably, the chlorinated hydrocarbon repair material is in powder, granular or block form.

10. A method for preparing the chlorinated hydrocarbon repair material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: S1. Under the protection of an inert atmosphere, organic matter A is first mixed with an organic solvent, and then the obtained first mixed solution is second mixed with organic matter B and organic matter C; S2. Drying the second mixed solution obtained in step S1.

11. The method according to claim 10, characterized in that In step S1, the weight ratio of the organic matter A, the organic matter B and the organic matter C is 30:0.5-20:0.1-3.

12. The method according to claim 10 or 11, characterized in that: In step S1, the ratio of the organic substance A to the organic solvent is 5-50 g:100 mL, preferably 10-30 g:100 mL; Preferably, in step S1, the organic solvent is one or more of ethanol, ethyl acetate and dichloromethane.

13. The method according to any one of claims 10 to 12, characterized in that: In step S1, the first mixing conditions include: a temperature of 35 to 85°C, preferably 50 to 65°C; Preferably, in step S1, the second mixing conditions include: a temperature of 35 to 85°C, preferably 65 to 70°C.

14. The method according to any one of claims 10 to 13, characterized in that: In step S2, the drying conditions include: a temperature of 40-100°C, preferably 50-70°C.

15. The method according to any one of claims 10 to 14, characterized in that: Step S2 further comprises: drying the solid block product obtained in step S2, and then optionally crushing the solid block product to obtain a powdered material; Preferably, the particle size of the powdered material is 10 to 1000 μm.

16. The method according to any one of claims 10 to 15, characterized in that: Step S2 further comprises: drying the step S2 to obtain a gel-like product, then shaping the gel-like product to obtain spherical particles, freeze-drying the spherical particles to obtain a granular material, and then optionally crushing the granular material to obtain a powdery material; Preferably, the freeze-drying conditions include: a temperature of -30 to -40°C and a time of 2 to 8 hours; Preferably, the particle size of the powdery material is 10 to 1000 μm.

17. A chlorinated hydrocarbon repair material prepared by the method of any one of claims 10 to 16; Preferably, the chlorinated hydrocarbon repair material is suitable for high permeability sites with a permeability coefficient greater than 1 m / d and special sites with high permeability in fractured aquifers.

18. A method for in-situ remediation of chlorinated hydrocarbons in an aquifer, characterized in that: The method comprises: mixing chlorinated hydrocarbon remediation materials, water and a quick-start agent, and then injecting the obtained mixed solution into a chlorinated hydrocarbon-contaminated water layer of an aquifer; The chlorinated hydrocarbon repair material is the chlorinated hydrocarbon repair material according to any one of claims 1 to 9 or the chlorinated hydrocarbon repair material according to claim 17; The quick-start agent is selected from one or more of lactic acid, alginate, ethanol, ascorbic acid, citric acid and glucose.

19. The method according to claim 18, characterized in that The weight ratio of the chlorinated hydrocarbon repair material to water is 1:2 to 20, preferably 1:2 to 15; Preferably, the weight ratio of the chlorinated hydrocarbon repair material to the quick-start agent is 10 to 50:1, preferably 10 to 30:

1.

20. The method according to claim 18 or 19, characterized in that The method further comprises: adding a pH value adjusting agent during the mixing of the chlorinated hydrocarbon repair material, water and the quick start agent; Preferably, the pH adjuster is selected from one or more of Ca(OH)2, Mg(OH)2, CaCO3, MgCO3, Na2CO3 and NaHCO3, preferably CaCO3 and / or MgCO3.

21. The method according to any one of claims 18 to 20, characterized in that: The chlorinated hydrocarbon is selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane, trichloropropane, dichloropropane, trichlorobenzene, dichlorobenzene and ethyl chloride.

22. A method for in-situ remediation of chlorinated hydrocarbons in an aquifer, characterized in that: The method comprises: mixing a chlorinated hydrocarbon remediation material and a quick-start agent, and then placing the resulting mixture in a permeable reaction wall of a chlorinated hydrocarbon-contaminated water layer of an aquifer; The chlorinated hydrocarbon repair material is the chlorinated hydrocarbon repair material according to any one of claims 1 to 9 or the chlorinated hydrocarbon repair material according to claim 17; The quick-start agent is selected from one or more of lactic acid, alginate, ethanol, ascorbic acid, citric acid and glucose.

23. The method according to claim 22, characterized in that The weight ratio of the chlorinated hydrocarbon repair material to the quick-start agent is 10 to 50:1, preferably 10 to 30:

1.

24. The method according to claim 23, characterized in that The chlorinated hydrocarbon is selected from one or more of carbon tetrachloride, tetrachloroethylene, trichloroethylene, dichloroethylene, tetrachloropropane, trichloropropane, dichloropropane, trichlorobenzene, dichlorobenzene and ethyl chloride.

Citation Information

Patent Citations

  • Nano emulsification carbon source with low aquifer permeability loss in groundwater remediation and preparation method thereof

    CN108675435A

  • Emulsified vegetable oil as well as preparation method and application thereof

    CN109534517A

  • Zero-valent iron and biochar source composite chemical for in-situ remediation of groundwater contaminated with chlorinated hydrocarbons

    CN107352657A

  • Polylactic acid and lactide blended sustained-release material

    CN112552664A

  • Biological permeable reactive barrier slow-release filler capable of removing trichloroethylene in underground water in situ and with core-shell structure and preparation method of biological permeable reactive barrier slow-release filler

    CN112960765A